Spain as a Reference in Wine Culture - E. V. Astakhova (Концепт: философия, религия, культура, 2021)
The culture of wine as a traditional drink in the countries of Southern Europe is determined by the geographical, ethnographic, and historical context, at the same time it is associated with national identification. In the case of Spain, wine plays the role of a friendly union, an element of active communication, is a sociocultural behavioral norm. Through the history of wine-making, the key stages of the country’s development can be traced: from ancient settlements to the European Union, variety of backgrounds, traditions and religions, etc. adding to the long history of wine on the territory of today’s Spain. The theme of wine is reflected in the works of famous Spanish philosophers, writers and artists as a stable tradition, a symbol of community, celebration, creativity, at the same time melancholy and sadness, as a typical Spanish dualism of attitude to life. It is noted that wine was not only viewed as a means of recreation, but also a powerful double-edged social factor, both pacifying and disorganizing. Taverns became people’s universities, and cafes with their tertulias became the center of intellectual life. Wine is an important economic component, the vineyard zones cover the whole country, with its main wine-making regions — from Rioja to Jerez — renowned around the world. Hundreds of varieties of wines are produced, which differ in denomination, aging, reputation, and popularity on the world market and with tourists. Spain has a leading position in this area. At present, bars, restaurants, and taverns, as public spaces suitable for big parties and family gatherings alike, have become not only a place of spending one’s pastime, but also a platform for political discussions, a place where certain political forces manipulate their influence, where polar views on the current and future agenda are in confrontation: the globalization of the society and cultural unification, or the preservation of unique customs and traditions. Wine culture is dynamic, it manifests itself in a new form in the younger generation, the latest gender and progressive norms appear, the simple, down-to-earth consumption characteristic of the bar culture displaces the spiritual component. The loss of traditions, including the wine culture, is dangerous for the society. It will have negative consequences for the country, will cause damage to its attractiveness for investors and tourists, and hurt the very image of their motherland the Spanish hold dear. Wine remains an important part of the national heritage, material, and spiritual culture of Spain.